The Action of 2-Aminoethyldiphenyl Borinate on the Pulmonary Arterial Hypertension and Remodeling of High-Altitude Hypoxemic Lambs - Castillo-Galán, Sebastián; Parrau, Daniela; Hernández, Ismael; Quezada, Sebastián; Díaz, Marcela; Ebensperger, Germán; Herrera, Emilio A.; Moraga, Fernando A.; Iturriaga, Rodrigo; Llanos, Aníbal J.; Reyes, Roberto V. (Frontiers in Physiology, 2022)
Calcium signaling is key for contraction, differentiation, and proliferation of pulmonary arterial smooth muscle cells. Further, calcium influx through store-operated channels (SOC) is particularly important in the vasoconstrictor response to hypoxia. Previously, we found adecrease in pulmonary hypertension and remodeling in normoxic newborn lambs partially gestated under chronic hypoxia, when treated with 2-aminoethyldiphenylborinate (2-APB), a non-specific SOC blocker. However, the effects of 2-APB are unknown in neonates completely gestated, born and raised under environmental hypoxia. Accordingly, we studied the effects 2-APB-treatment on the cardiopulmonary variables in lambs under chronic hypobaric hypoxia. Experiments were done in 9 newborn lambs gestated, born, and raised in high altitude (3600 m): 5 animals were treated with 2-APB (i.v. 10 mg.kg-1) for 10 days whilst other 4 animals received vehicle. During the treatment, cardiopulmonary variables were measured daily, and these were also evaluated during an acute episode of superimposed hypoxia, one day after at the end of the treatment. Furthermore, pulmonary vascular remodeling was assessed by histological analysis two days after the end of the treatment. Basal cardiac output and mean systemic arterial pressure and resistance from 2-APB- and vehicle-treated lambs did not differ along the treatment. Mean pulmonary arterial pressure (mPAP) decreased after the 1st day of 2-APB treatment and remained lower than the vehicle-group until 3rd day, and during the 5th, 6th and 9th day of treatment. The net mPAP increase in response to acute hypoxia did not change, but pressure area under curve during hypoxia was slightly lower in 2-APB- than vehicle lambs. Moreover, 2-APB treatment decreased the pulmonary arterial wall thickness, the α-actin immunoreactivity and increased the luminal area with no changes in the vascular density. Our findings show that 2-APB-treatment partially reduced the contractile hypoxic response and revert the pulmonary vascular remodeling, but this is not enough to normalize the pulmonary hemodynamics in chronically hypoxic newborn lambs.